Effects of plant growth retardant daminozide (Alar) on neuromuscular co-ordination behavior in Drosophila melanogaster. Issue 22 (17th November 2022) - Das, Debasmita; Begum, Morium; Paul, Pallab; Dutta, Ishita; Mandal, Sayarneel; Ghosh, Papiya; Ghosh, Sujay
ABSTRACT: Daminozide (alar), a plant growth retardant, is used in different fruit orchard to make fruits attractive and reduce pre-harvest losses. Previously data demonstrated that acute daminozide exposure affected reproductive fitness and produced neurodegeneration in Drosophila melanogaster . The goal of this study was to determine whether continuous exposure to daminozide affects neuromuscular co-ordination in D. melanogaster as manifested in various behavioral responses. Fruit flies were exposed to 200 or 400 mg/L concentration of daminozide for two successive generations. Treated D. melanogaster were examined for the behaviors indicative of neuromuscular coordination and cognitive abilities, that include climbing, social interaction, adult grooming, migration, flight, male aggression, and adult courtship. Aberrant behavioral responses were noted among treated D. melanogaster of both sexes as evidenced by the following parameters: reduction in flight duration, abnormal social interaction, altered copulatory acts, and over-aggressiveness. Data suggest that daminozide produces impairment in neuromuscular coordination and cognitive ability in Drosophila, which was reflected as altered behavioral patterns. As Drosophila is considered as a reliable in vivo model utilized in toxicity testing, our findings may help us to anticipate and monitor potential daminozide-induced toxicity in animals and humans.